2016
DOI: 10.1123/jsm.2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Sport Consumer Behavior Research: Improving Our Game

Abstract: Sport consumer behavior (SCB) research continues to grow in both popularity and sophistication. A guiding principle in much of this research is that sport consumers seek out sport-related experiences, and the benefits they yield, in order to satisfy needs and wants. This approach has provided new knowledge and insight into sport consumers. One outcome of this focus is that the vast majority of research on sport consumers has centered on psychological characteristics of these sport experiences related to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…The results indicated that fans were motivated to attend a game when they already identified the team. These data supports the previous claim that team identification is a key predictor of sport consumption behaviour (D. Funk et al, 2016;D. C. Funk, 2017;E.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results indicated that fans were motivated to attend a game when they already identified the team. These data supports the previous claim that team identification is a key predictor of sport consumption behaviour (D. Funk et al, 2016;D. C. Funk, 2017;E.…”
Section: Discussionsupporting
confidence: 91%
“…As Wang et al, (Wang et al, 2011) believed that a team-dependent factor is not solely enough to predict the consumers' behaviour without considering the satisfaction. From a wider perspective, social interaction is a key determinant of sport participation (D. Funk et al, 2016;D. C. Funk, 2017;Yoshida, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature on the role of emotions in the sport business was very limited until a few years ago ( Wolfe et al, 2005 ), it has currently become the central axis of the sport business in contemporary societies ( Rodriguez-Pomeda et al, 2017 ). In fact, the sport consumer has become a popular area of study for sport management researchers ( Funk et al, 2016 ) in which the importance of consumer satisfaction and emotions to enhance loyalty has been highlighted ( Koenig-Lewis and Palmer, 2014 ). This focus has developed because knowing customers’ emotions and the way they express them allows sport managers to act on these emotions and reproduce them in an efficient way, with the aim of influencing and guiding them for the benefit of the organization ( Puig, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Desde el punto de vista de la oferta son habituales los estudios relativos a la gestión y organización de eventos deportivos (Magaz-González & Fanjul-Suárez, 2012). Por su parte, en el campo de la economía aplicada que estudia la demanda, muchos estudios han analizado el consumo desde el punto de vista de espectador de espectáculos deportivos (Doyle, Filo, Lock, Funk, & McDonald, 2016;Funk, Lock, Karg, & Pritchard, 2016), utilizando instrumentos de medida de su calidad percibida y de sus intenciones futuras (Calabuig Moreno, Crespo Hervás, Núñez-Pomar, Añó Sanz, & Prado-Gascó, 2015) o comprobando la elasticidad de la demanda en función de los precios (Calabuig, Núñez-Pomar, Añó, & Prado-Gascó, 2014). También se han realizado estudios sobre la importancia de las redes sociales en la toma de decisiones del consumidor deportivo (García-Fernández, Fernández-Gavira, Durán-Muñoz, & Vélez-Colón, 2015).…”
Section: Introductionunclassified